Effects of geometric parameters on sound absorption performance of acoustic metasurface with subwavelength thickness - Baydur, Caner; Bayraktar, Meral (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2024)
Conventional sound-absorbing materials such as mineral wool and perforated panels have inadequate acoustic performance in the low-frequency region. On the other hand, acoustic metasurfaces can provide high absorption with subwavelength thickness in the desired frequency range according to their structural properties. Herein, we present the effects of changes in geometric parameters of a sound-absorbing metasurface on acoustic performance. The metasurface consists of a perforated panel in its outer layer and coiled-up channels behind the panel. The impacts of hole numbers, panel thickness, hole diameter and channel depth parameters on sound absorption performance were examined. Acoustic analyses were performed with the Pressure Acoustics module of COMSOL MultiPhysics. Theoretical and numerical results are in agreement. The metasurface provides perfect sound absorption in the desired frequency range with an ultra-thin scale. That makes it an alternative to traditional materials in room acoustics and noise control.
Keywords: Acoustic metasurface; Perfect absorption; perforated panel; coiled-up channel; MICRO-PERFORATED PANEL; ABSORBERS; DESIGN; Engineering